A CONCEPTUAL STUDY ON EFFECT OF VISHANGHAN MAHAKSHAYA ON VISHJANYA ALLERGIC SKIN DISORDERS - Sason, *Rajveer; Sharma, Anita; Arya, Neelam (International Journal of Ayurveda and Pharma Research, 2016)
As per the Ayurvedic treaties, Visha means the Dravya (substance) which causes Vishaad (sorrow or depression) is known as Visha. Drugs which act against toxic substances are called as Vishghna (Anit-toxic). Charakacharya described Vishghna mahakashaya which includes ten drugs having Anti-toxic action. The main objective of this review article is to discuss the therapeutic uses of Vishghna Mahakashaya and to discuss the different pharmacological properties and therapeutic uses of isolated constituent drugs of Vishghna Mahakashaya in respect to Vishjanya skin disorders. Vishghna Mahakashaya is described by Acharya Charak for the management of various diseases produced due to deterious effect of Vish. It includes Haridra (Curcuma longa), Manjishtha (Rubia cordifolia), Suvahaa (Pluchea lanceolata ), Sookshama elaa (Elettaria cardamomum), Paalindee (Operculina turpethum), chandan (Santalum album), Kataka (Strychnos potatorum), Shireesh (Albizzia lebbeck), Sinduvaara (Vitex negundo), Shleshmaataka (Cordia dichotoma). Drugs like Haridra, Manjistha, Chandan, Shirish, Shleshmaataka have very tremendous properties on various skin disorders like allergy. As per old sages, these drugs are useful in the treatment of all types of poisoning especially snake bite, scorpion bite, spider bite, rat bite, insect bite. Present paper highlights on various pharmacological properties of individual drugs of Vishghna mahakashya especially those properties due to which they can be used in various Vishjanya vikaar.